THE INFLUENCE OF QUALITY OF WORK LIFE, ORGANIZATIONAL CITIZENSHIP BEHAVIOR, AND COMMUNICATION ON EMPLOYEE PERFORMANCE AT CV. MADIUN CREATIVE INDUSTRY - Husodo, Putra Febrianto; Widhianingrum , Wahna; Wardhani, Diana Pramudya (Proceeding of International Conference on Social Science and Humanity, 2024)
General Background: Effective communication, teamwork, and leadership are pivotal elements influencing employee performance in contemporary organizations. Specific Background: However, there is limited empirical evidence on the distinct and combined impacts of these factors in specific organizational contexts. Knowledge Gap: The literature lacks focused studies on how these variables interact to affect employee performance, particularly in Indonesian companies. Aims: This study aims to examine the effect of communication, teamwork, and leadership on employee performance at PT Syncore Indonesia using a quantitative approach. Results: Utilizing SPSS for data analysis, the study found that communication, teamwork, and leadership are positively and significantly correlated with employee performance. Specifically, effective communication enhances task clarity and reduces misunderstandings, improving performance. Good teamwork fosters efficiency and innovation, while supportive leadership boosts motivation and commitment. Novelty: The research contributes novel insights by demonstrating the individual and interactive effects of these variables in a specific organizational setting, thereby filling a gap in the existing literature. Implications: The findings underscore the importance for PT Syncore Indonesia to continuously develop communication strategies, foster teamwork, and implement supportive leadership practices to enhance overall employee performance. This study provides practical implications for management to formulate strategies and policies aimed at improving productivity and organizational effectiveness.